Air Gap Effect on the Properties of Unsaturated Symmitrical Double Polepiece Lenses - Hasan, H. S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The preferable design for unsaturated symmetrical spherical double-pole piece electron lens required good focal properties, and in this present study investigate effect of air gap wide (S) on the properties of the projector lens specialized the minimum projector focal length 1Fr) . and the properties of the axial magnetic field lnlll distribution:(the maximum value of magnetic flux density Bm and total half width of magnetic field curve W) , and at lowest values of mm (Fr) . at low values of (S) will be obtained high magnification and there is an importance indicator for preferable lens design which is used in transmission electron microscope (TEM).